Analiticidade de funções diferenciáveis em quase todo ponto - Andrade, Nícolas Alcântara de (2015)
This work is based on the article Analyticity Of Almost Everywhere Differentiable Functions, it will develop a partitioning lemma for superadditive set functions which will lead to a simple alternative proof of Besicovitch’s theorems.